Omega-3 fatty acid supplementation can improve both symptoms and signs of dry eye disease - Kwon J (Dove Medical Press, 2017)
Jae-Woo Kwon,1 Sang Beom Han2 1Department of Internal Medicine, 2Department of Ophthalmology, Kangwon National University Hospital, Kangwon National University Graduate School of Medicine, Chuncheon, South Korea We read with great interest the article by Gatell-Tortajada1 entitled “Oral supplementation with a nutraceutical formulation containing omega-3 fatty acids, vitamins, minerals, and antioxidants in a large series of patients with dry eye symptoms: results of a prospective study”. The prospective large-scale study was undoubtedly well designed and conducted, and the authors should be congratulated for successfully demonstrating that oral omega-3 fatty acid supplementation can be an effective treatment for dry eye symptoms.1The authors showed that supplementation of omega-3 fatty acids improved dry eye signs, such as corneal erosion, tear film breakup time, and conjunctival hyperemia, suggesting that they can reduce ocular surface inflammation and also alleviate dry eye symptoms.1 Rashid et al2 also demonstrated that topical application of omega-3 fatty acids led to a decrease in dry eye signs and inflammatory changes at both cellular and molecular levels.  View original paper by Gatell-Tortajada